Mammalian amyloidogenic proteins promote prion nucleation in yeast - Chandramowlishwaran, Pavithra; Nussbaum-Krammer, Carmen (The journal of biological chemistry, 2018)
Fibrous cross-β aggregates (amyloids) and their transmissible forms (prions) cause diseases in mammals (including humans) and control heritable traits in yeast. Initial nucleation of a yeast prion by transiently overproduced prion-forming protein or its (typically, QN-rich) prion domain is efficient only in the presence of another aggregated (in most cases, QN-rich) protein. Here, we demonstrate that a fusion of the prion domain of yeast protein Sup35 to some non-QN-rich mammalian proteins, associated with amyloid diseases, promotes nucleation of Sup35 prions in the absence of pre-existing aggregates. In contrast, both a fusion of the Sup35 prion domain to a multimeric non-amyloidogenic protein and the expression of a mammalian amyloidogenic protein that is not fused to the Sup35 prion domain failed to promote prion nucleation, further indicating that physical linkage of a mammalian amyloidogenic protein to the prion domain of a yeast protein is required for the nucleation of a yeast prion. Biochemical and cytological approaches confirmed the nucleation of protein aggregates in the yeast cell. Sequence alterations antagonizing or enhancing amyloidogenicity of human amyloid-β (associated with Alzheimer's disease) and mouse prion protein (associated with prion diseases), respectively, antagonized or enhanced nucleation of a yeast prion by these proteins. The yeast-based prion nucleation assay, developed in our work, can be employed for mutational dissection of amyloidogenic proteins. We anticipate that it will aid in the identification of chemicals that influence initial amyloid nucleation and in searching for new amyloidogenic proteins in a variety of proteomes.
Gesehen am 09.04.2019